Implementasi Metode OEE untuk Mengatasi Ketidakstabilan Kinerja Mesin Produksi Produk Kosmetik Cair pada Industri Kosmetik - Ilhami, Viga Aura Graziella; Tranggono, Tranggono (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The cosmetic industry is a company engaged in the cosmetics sector, in this case the company produces liquid cosmetic products that must achieve targets every month. However, due to the monthly target system, the company does not carry out maintenance on its machines so that the machines are damaged. Therefore, this study focuses on the analysis of the effectiveness of liquid product production machines in the cosmetics industry so that the production process runs well and in accordance with the specified targets. This study uses the Overall Equipment Effectiveness (OEE) method. With data obtained from historical results for the 2024 period, this method is used to determine machines that require ongoing maintenance that can affect the production process. To facilitate the calculation, this study uses Microsoft Excel software. The OEE calculation results in January were 98.61%. The percentage results for January, February, March, April, June, July, August, September are values ​​that are in accordance with the word class standard because the percentage value is above 85%, but in May and October are percentage values ​​that do not comply with the word class standard criteria because the value is below 85% so that May and October require ongoing maintenance because they have not met the word class standard. Keywords: Effectiveness, Maintenance, Percentage, Production, Standard